PENGARUH MUTU PELAYANAN KEPERAWATAN TERHADAP PERSEPSI PASIEN RAWAT INAP DI RSU BANDUNG MEDAN - Mailisa, Wan Ria; Ginting, Daniel; Silitonga, Evawani M. (TOUR HEALTH JOURNAL, 2024)
Background: The problem that is often found is that patients do not get the service they should, they wait too long. The inpatient rooms are class III including wards in RSU Bandung, namely rooms consisting of 2 and 4 rooms with a capacity of 10-15 patients in one room. Based on information from Bandung Hospital, inpatients' perceptions of good nurse services, especially class III or wards, are around 60%. Purpose: The purpose of this research is to find out what strategies are used in improving the quality of nursing services based on the perception of inpatients in Bandung General Hospital 2019. Method: The sample in this study was the entire population of 89 people. This type of research uses descriptive correlation with cross sectional approach. Results : Based on the test results it can be concluded that there is a significant influence between reliability on the perception of inpatients. There is a significant influence between responsiveness on the perception of inpatients. There is a significant influence between assurance on inpatient perceptions. There was no significant influence between empathy on the perception of inpatients. There was no significant effect between tangibles on the perception of inpatients. Disscusion and Conclusion: The author suggests that in order to make this research more accurate, researchers should further add research variables and increase the number of samples. Patients should really pay attention to the satisfaction of nursing staff in the hospital to feel comfortable when treated. Bandung Hospital should improve their nursing care services as well as possible.